Potassium Solubilizing Microorganisms for Sustainable Agriculture 2016
DOI: 10.1007/978-81-322-2776-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-Solubilizing Bacteria and Their Application in Agriculture

Abstract: Potassium (K) is one of the major macronutrients which play an important role in plant growth and development. Total soil potassium reserves are generally large; however, major portion of it exists in insoluble K minerals and very little potassium becomes available to plants. There are certain microorganisms which use a number of biological processes to make potassium available from unavailable forms. These potassiumsolubilizing bacteria (KSB) can be used as a promising approach to increase K availability in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(57 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…Other macronutrients, TP and TK, were significant lower in SKRD than those of in NKRD areas, indicating nutrient limiting condition in SKRD soils. Interestingly, AK was significantly higher in degraded soils, which might due to the predominance and contributions of KSB, such as Pseudomonas, Bacillus , and Burkholderia (Ahmad et al, 2016 ). Overall, we find that soil quality in SKRD region significantly decreased compared to that of in NKRD area.…”
Section: Discussionmentioning
confidence: 99%
“…Other macronutrients, TP and TK, were significant lower in SKRD than those of in NKRD areas, indicating nutrient limiting condition in SKRD soils. Interestingly, AK was significantly higher in degraded soils, which might due to the predominance and contributions of KSB, such as Pseudomonas, Bacillus , and Burkholderia (Ahmad et al, 2016 ). Overall, we find that soil quality in SKRD region significantly decreased compared to that of in NKRD area.…”
Section: Discussionmentioning
confidence: 99%
“…pathogens), or neutral for the plant, and sometimes the impact of a bacterium may vary as the soil conditions change (Cheng et al, 2010). The bacteria that provide some (Ahmad et al, 2016;Bakhshandeh et al, 2017;Gundala et al, 2013;Meena et al, 2014). There are strong evidences that soil bacteria are capable of transforming soil K to the forms available to plant effectively (Meena et al, 2015a;Meena et al, 2014;Meena et al, 2016).…”
Section: Bacteria-soil-plant Interactionsmentioning
confidence: 99%
“…It has been reported that inoculation with KSB produced beneficial effect on growth of different plants (Ahmad et al, 2016;Bakhshandeh et al, 2017;Xiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By inoculating these microbial strains into the soil where the crops are grown, not only will the bioavailability of Zn be improved, but we can also promote a sustainable agro-ecosystem. Through the siderophore and exopolysaccharide production, nutrient solubilization, the production of organic acids and phytohormones, the mobilization of nutrients, and the fixation of atmospheric nitrogen carried out by these microbes, the availability of Zn can be raised, thus helping plants to uptake more Zn from the soil [87]. Significant increases in Zn contents in maize grains were observed when the crop was grown in soil inoculated with the bacterial strains from the genera Azotobacter, Pseudomonas, Bacillus, and Azospirillum [88,89] [SaCS20]), the bioavailability of Zn in the soil was significantly enhanced, resulting in higher levels of Zn in the grains and the yields were also improved [29,90,91].…”
Section: Zinc (Zn) Deficiency Can Be Eradicated Using Soil Microbesmentioning
confidence: 99%